2011
DOI: 10.1371/journal.pone.0024629
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Tuberculosis Prevalence Survey on Cattle in the Rural Livestock System of Torodi (Niger)

Abstract: BackgroundBovine tuberculosis (BTB) is a widespread zoonosis in developing countries but has received little attention in sub-Saharan Africa, especially in Niger. Recent investigations confirmed the high incidence of the disease in cattle slaughtered in an abattoir in Niamey. The fact that most of the animals in which M. bovis has been identified were from the rural area of Torodi implied the existence of a probable source of BTB in this region. This study aimed to determine the prevalence of BTB infection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
(39 reference statements)
3
24
1
1
Order By: Relevance
“…Thus, it is evident that the initial thickness of the skin fold could confuse the interpretation of reactivity to tuberculin. In Africa, some authors have found relatively low rates ranging from 2 to 6% (Boukary et al, 2011;Boussini et al, 2012;Katale et al, 2013;Muma et al, 2013). In contrast, in Nigeria, Okeke et al (2014) found 16.17% with PCR on cattle lungs taken from slaughterhouses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is evident that the initial thickness of the skin fold could confuse the interpretation of reactivity to tuberculin. In Africa, some authors have found relatively low rates ranging from 2 to 6% (Boukary et al, 2011;Boussini et al, 2012;Katale et al, 2013;Muma et al, 2013). In contrast, in Nigeria, Okeke et al (2014) found 16.17% with PCR on cattle lungs taken from slaughterhouses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, areas that are currently invaded by Prosopis were important sources of forage for livestock in the dry season, leading to shrinkage of the range-and grasslands, and altering local host densities, and increasing contact among cattle herds. For instance, increased host movement have been repeatedly identified as one of the major risk factors for bTB infection in African cattle populations [35,36,37]. We, therefore, hypothesize that increasing Prosopis invasion can increase the risk of bTB infection by increasing contact among cattle herds.…”
mentioning
confidence: 87%
“…higher in peri-urban vs. extensive systems [67]). In addition, as for Central Africa, no reliable data is available regarding wildlife.…”
Section: West Africamentioning
confidence: 99%
“…2; adapted from [33,53,[77][78][79][80][81]) include the type of production system (intensive, dairy farms, use of upgraded B. taurus breeds), animal movements (herds importing animals, transhumance) and absence or inefficiency of bTB surveillance and control. Several studies have analysed bTB risks of transmission between livestock and humans [58,67,75,80,82], identifying husbandry practices (housing, mixing cattle herds with other small ruminants), food preferences (consumption of raw or soured milk) and overall health and hygienic conditions (HIV) as the main risk factors for humans (Fig. 2).…”
Section: Conceptual Model Of Btb Transmission At the Wildlife-livestomentioning
confidence: 99%